ASSESSMENT OF DRUG INTERACTION AND ADVERSE DRUG REACTION IN PATIENTS OF CHRONIC KIDNEY DISEASE WITH HEMODIALYSIS (Journal of Medical & Health Sciences Review, 2025)
Chronic kidney disease (CKD) is the presence of kidney damage or an estimated glomerular filtration rate of less than 60 mL/min/1.73 m², persisting for 3 months or more. The incidence of chronic kidney disease increases all over the world, It was ranked 27th in the list of causes of total number of worldwide deaths in 1990, but rose to 18th in 2010.Descriptive cross sectional study in Khyber teaching hospital Peshawar conducted to assess medication interactions and adverse drug reactions (ADRs) in chronic kidney disease patients undergoing hemodialysis. According to the prevalence of chronic renal disease by age, the lowest age of patients was 16 and the highest was 86. According to this survey, 46 is the average age. The findings indicate that of the fifty (50) patients with CKD, twenty-eight (56%) are female, and twenty- two (44%) are male. The majority of the patients were from the Peshawar region. The most commonly used drugs in the Nephrology ward were cefoperazone + sulbactam, omeprazole, soda mint, iron poly-maltose complex with folic acid, furosemide, and other drugs were given according to their comorbid condition. The most common lab abnormalities were blood urea, hemoglobin, and creatinine levels, the study shows that in all patients these parameters are not in the normal range. ADRs were not reported in all the cases, Drug interactions were identified, with some cases exhibiting major interactions, underscoring the need for careful drug management. Majority of patients are of older age and female, adverse drug reaction were not reported in that patient but durg interaction were determined so proper care is needed in chronic kidney disease patient during hemodialysis.